Effect of zinc supplementation on growth hormone secretion, IGF-I, IGFBP-3, somatomedin generation, alkaline phosphatase, osteocalcin and growth in prepubertal children with idiopathic short stature - BEREKET, ABDULLAH; HAKLAR, GONCAGÜL; DEMİRCİOĞLU, SERAP (My University, 2005)
Controversy exists about the effect of zinc on growth and the GH-IGF system. Zinc supplementation has been shown to stimulate linear growth in zinc-deficient children. However the mechanism of this effect has not been well characterized. Furthermore, the effect of zinc supplementation on non-zinc-deficient short children is unknown. We investigated the effect of zinc supplementation on endogenous GH secretion, serum IGF-I and IGFBP-3 concentrations, IGF-I and IGFBP-3 generation in response to exogenous GH, bone formation markers, and linear growth of non-zinc-deficient children with idiopathic short stature. We analyzed prospectively serum zinc, IGF-I, IGFBP-3, alkaline phosphatase, osteocalcin, and GH response to clonidine test, and performed a somatomedin generation test before and 6 weeks after zinc supplementation in 22 (16 M, 6 F) prepubertal children with idiopathic short stature. Serum IGF-I increased from 67.4+/-70.6 to 98.2+/-77.3 ng/ml (p <0.001), IGFBP-3 from 2326+/-770 to 2758+/-826 ng/ml (p <0.001), alkaline phosphatase from 525+/-136 to 666+/-197 U/l (p <0.0001), and osteocalcin from 16.8+/-10.6 to 25.8+/-12.8 ng/ml (p <0.05) after zinc supplementation despite there being no difference in GH response to clonidine after zinc supplementation (peak GH 11.6+/-6.9 vs 13.4+/-7.8 ng/ml, GH area under the curve during clonidine test 689+/-395 vs 761+/-468, NS). Percent change in IGF-I and IGFBP-3 during the somatomedin generation test was not significantly affected by zinc supplementation (118% vs 136% and 57% vs 44%, respectively). There was no significant correlation between percentage increase in zinc levels and percentage increase in parameters tested. Height SDS or weight SDS did not improve significantly in 17 patients who continued on zinc supplementation for at least 6 months (6-12 months) (-2.59 vs -2.53 SDS and -1.80 vs -1.67 SDS, respectively). Zinc supplementation increased basal IGF-I, IGFBP-3, alkaline phosphatase and osteocalcin without changing GH response to clonidine. Zinc supplementation did not affect sensitivity to exogenous GH as tested by IGF-I and IGFBP-3 generation test. These results suggest a direct stimulatory effect of zinc on serum IGF-IGFBP-3, alkaline phosphatase and osteocalcin. Despite improvements in the above parameters, zinc supplementation to children with idiopathic short stature with normal serum zinc levels did not significantly change height or weight SDS during 6-12 months follow-up.
Keywords: Female; Humans; Treatment Outcome; Male; Child; Growth Disorders; Prospective Studies; Alkaline Phosphatase; Dietary Supplements; Human Growth Hormone; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Osteocalcin; Puberty; Somatomedins; Zinc